Linearized solar elastosis of the legs: A novel presentation and review of the literature. (15th August 2018) - Cheng, Judy; Ho, Jonathan; Barrett, Mary; Chung, Hye J.; Lam, Christina
Abstract : There exists a spectrum of solar elastotic variants based on the clinical and histopathologic findings. We present here a peculiar case of solar elastosis that is unusual in its anatomic location, relative lack of background actinic damage, and pattern of linearization. Its presentation suggests that other factors in addition to ultraviolet radiation may play a role in the pathogenesis of solar elastosis.